Research on the development and performance of new high-brisance emulsion explosives - M. R. Du; T. D. Xuan; Z. F. Chen; W. W. Li; L. Yuan; B. X. Zheng (Scientific Reports)
Abstract This study developed a novel high-brisance emulsion explosive containing sodium borohydride (NaBH4). The effects of NaBH4 content on the performance of the emulsion explosive were investigated using methods such as brisance, detonation velocity, air shock wave analysis, density measurement, and theoretical calculations. And the thermal decomposition characteristics of emulsion explosives samples were investigated using thermogravimetric (TG) experiments. The results indicate that as the NaBH4 content increases, the explosive density initially increases and then decreases, the detonation velocity gradually decreases, the explosive heat continuously increases, and the explosion volume first increases slightly and then decreases. Brisance, influenced by multiple factors including density, detonation velocity, explosive heat, and explosion volume, also shows a trend of first increasing and then decreasing. When the NaBH4 content is 5%, the brisance reaches its maximum value (26.3 mm), representing a 66.5% improvement compared to conventional emulsion explosives and surpassing existing high-brisance emulsion explosives. Furthermore, with increasing NaBH4 content, the peak overpressure of the air shock wave initially decreases and then increases. The TG and derivative thermogravimetry (DTG) curves of all samples exhibit consistent trends. Under the same heating rate, the addition of NaBH4 raises the initial decomposition temperature of the emulsion explosive.